The Strategy of Islamic Religious Education Teachers in Enhancing Students’ Intrinsic Learning Motivation through Game-Based Learning Using Sticky Note Media in Asmaul Husna Material for Grade 3 at MHM Dayamurni Excellent Islamic Elementary School - Septi Wulandari; Ehwanudin Ehwanudin; Mai Zuniati (Journal of Research in Islamic Education, 2026)
This study aims to explore the strategies of Islamic Religious Education teachers in enhancing students’ intrinsic learning motivation through Game-Based Learning (GBL) assisted by sticky note media in teaching Asmaul Husna. The primary issue underlying this research is the dominance of conventional methods, particularly mechanistic memorization, which has led to low student engagement and limited intrinsic motivation in the classroom. This study employed a qualitative research design with a descriptive approach. The research subjects consisted of one Islamic Religious Education teacher and 21 third-grade students at MHM Dayamurni Excellent Islamic Elementary School. Data were collected through participatory observation, in-depth interviews, and documentation. The findings indicate that the implementation of Game-Based Learning (GBL) assisted by sticky note media significantly enhanced students’ intrinsic learning motivation, as reflected in increased interest, self-confidence, active participation, and enthusiasm during the learning process. The teacher’s structured, collaborative, and interactive strategy created an enjoyable and meaningful learning environment. Therefore, the use of GBL supported by simple media can serve as an effective alternative instructional strategy for improving students’ motivation in Islamic Religious Education at the elementary school level.